Explaining illness with evil: pathogen prevalence fosters moral vitalism. Issue 1914 (6th November 2019) - Bastian, Brock; Vauclair, Christin-Melanie; Loughnan, Steve; Bain, Paul; Ashokkumar, Ashwini; Becker, Maja; Bilewicz, Michał; Collier-Baker, Emma; Crespo, Carla; Eastwick, Paul W.; Fischer, Ronald; Friese, Malte; et al.
Abstract : Pathogens represent a significant threat to human health leading to the emergence of strategies designed to help manage their negative impact. We examined how spiritual beliefs developed to explain and predict the devastating effects of pathogens and spread of infectious disease. Analysis of existing data in studies 1 and 2 suggests that moral vitalism (beliefs about spiritual forces of evil) is higher in geographical regions characterized by historical higher levels of pathogens. Furthermore, drawing on a sample of 3140 participants from 28 countries in study 3, we found that historical higher levels of pathogens were associated with stronger endorsement of moral vitalistic beliefs. Furthermore, endorsement of moral vitalistic beliefs statistically mediated the previously reported relationship between pathogen prevalence and conservative ideologies, suggesting these beliefs reinforce behavioural strategies which function to prevent infection. We conclude that moral vitalism may be adaptive: by emphasizing concerns over contagion, it provided an explanatory model that enabled human groups to reduce rates of contagious disease.